Video Profile Promosi Dan Informasi Pada SMK Ariya Metta - Yuni Roza; Nanda Nanda; Gustina Gustina (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2019)
The development of the media information is evidenced by the number of communications and telecommunications pioneer who compete creates media information either through print media, television, even internet radio is very easy to reach by anyone without limit. With the importance of media information at this time, because through the medium of information the public can find out information or exchanging information to other communities as well as interacting with each other especially in the field of education, namely SMK ( Vocational High School). His research methods, namely: Data collection, Analysis, Problem analysis method of design Media, and Production method of the concept of Mavib (KPM) which include: PreProduction, Production, Multimedia Design, planning of Audio, Visual, and Perecanaan PostProduction. The results of his research in the form of promotional video CMS Ariya Metta Tangerang contained item images, motion, sound and music. So that through the promotion done, SMK Ariya Metta can be easily recognized community and was able to increase the number of registrants registrants.